Expert and knowledge systems and databases of the best practice - Kaklauskas, Artūras; Zavadskas, Edmundas Kazimieras; Gargasaite, Leonarda (Technological and Economic Development of Economy, 2004)
Investigations on the similarities and differences of expert, knowledge management and decision support systems are presented in the paper. Explicit and tacit knowledge is analysed. The benefit of knowledge management systems, their development and implementation are analysed. The aspects of the best practice and its knowledge bases and databases are described. Practical possibilities to apply the knowledge systems are presented. On the base of practice acquired during the FP 6 project INTELCITIES the database of the best practice and the web‐based decision support system for real estate are developed. On the base of the BPJTA in PuBs project the database of the best practice and the web‐based decision support system for retrofit of public buildings are developed.Article in Lithuanian.Ekspertinės ir žinių sistemos bei geriausios patirties duomenų bazėsFirst Published Online: 21 Oct 2010